225k views
4 votes
Let ​f(x)=3x-1 and ​g(x)=x squared+2. Find ​(f o ​g)(0​). Then ​(f o ​g)(0​)= ?

User Cdeterman
by
5.2k points

2 Answers

6 votes

Answer:

5

Explanation:

Evaluate g(0) then substitute the value obtained into f(x)

g(0) = 0² + 2 = 0 + 2 = 2, then

f(2) = 3(2) - 1 = 6 - 1 = 5

User Gowtham Sooryaraj
by
5.5k points
5 votes

Answer:

5.

Explanation:

To find (f o g)(x) we replace the x in f(x) by g(x):

(f o g)(x) = 3(x^2 + 2) - 1.

So (f o g)(0) = 3(0^2 + 2) - 1

= 6 - 1

= 5.

User Mukwux
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.